The role of gratitude in adolescents' psychological adjustment in cyberbullying situations - Chamizo-Nieto, María Teresa (UMA Editorial, 2023)
In last years, there has been an increase in the phenomenon of cyberbullying or online peer violence among adolescents around the world (Zhu et al., 2021). This phenomenon can be understood as aggressive or harmful behaviour by one person, or a group of people, towards others though the use of digital technology or electronic devices (Ansary, 2020). Numerous studies have shown evidence of the severe negative impact that adolescents involved can suffer on their health and well-being in different areas of their lives (e.g., social, academic, psychological, and personal; Camerini et al., 2020). Although cyberbullying is a global phenomenon, not all adolescents become involved in it nor do they suffer the same negative consequences on their health (e.g., Kwan et al., 2020). Therefore, possible strengths or personal resources that adolescents can develop to cope more adaptively with these adverse situations have been explored. Among them, gratitude has been shown to have beneficial effects on psychological adjustment and social functioning in adolescents (e.g., Bono et al., 2019; Portocarrero et al., 2020). Gratitude can be understood as the emotion that occurs when people perceive the help and good deeds that they receive from others, showing a motivation to respond kindly to those people (McCullough et al., 2002). Also, gratitude encompasses a broader concept, being considered a lifestyle or vital orientation in which people are aware of and appreciate the experiences that happen to them (Wood et al., 2010).
The benefits of gratitude on health are not only confined to everyday or positive situations. Previous research has shown that gratitude can also have protective effects in adverse and violence situations. For instance, gratitude can help to reduce aggressive behaviours in work, education, or prison contexts (e.g., Deng et al., 2019; García-Vázquez et al., 2020; Locklear et al., 2021) or buffer the development of psychological maladjustment in victims (e.g., Rey et al., 2019; Zhang & Wang, 2019). Nevertheless, in specific situations of violence, such as cyberbullying, gratitude has been little studied. A better understanding of the role of gratitude in these online violence contexts would contribute to improving the management and prevention of these adverse situations in adolescents. As consequence, this knowledge could help to improved adolescents’ quality of life and psychological adjustment. Therefore, the main purpose of this doctoral dissertation was to deepen and expand the existing knowledge of the role and benefits of the practice of gratitude towards cyberbullying situations in adolescents.
Keywords: Ciberacoso - Tesis doctorales; Psicología; Psicología del niño y del adolescente; Psicología diferencial; Afrontamiento de problemas personales